Maximizing effectiveness of reading comprehension instruction in diverse classrooms - Berkeley, Sheri; Taboada Barber, Ana. (Baltimore, Maryland : Paul H. Brookes Publishing Co., 2016)
"Comprehension is the ultimate goal of reading. In order for students to read and gain new understanding from texts, teachers must fully understand how to teach comprehension to a variety of learners. This supplemental textbook brings together a broad body of research on reading comprehension instruction for special education middle school and high school students in inclusive classrooms. It serves as a resource for classroom teachers as well as a practical, foundational supplemental text for undergraduate and master's level licensure programs. With its clear, research-based and applied instructional information, it will stand out in the marketplace as a text for novice teachers, both in-service and preservice. Chapters focus on a range of topics including helping students acquire new vocabulary, activating prior knowledge to make connections, utilizing reading comprehension strategies, asking questions while reading, and monitoring comprehension. By including vignettes, teaching materials, and activities, this book is an accessible, teacher-friendly volume that illustrates the most critical concepts for improving students' reading comprehension"--
Keywords: Reading comprehension; Language arts (Middle school); Language arts (Secondary); Children with disabilities -- Education; Special education; Inclusive education; LANGUAGE ARTS & DISCIPLINES / Literacy; LANGUAGE ARTS & DISCIPLINES / Reading Skills; EDUCATION / Inclusive Education